Società e Università Valutazione e Impatto Sociale - Blasi, Brigida (Associazione Italiana di Valutazione, 2023)
The book traces the main stages of third mission and social impact assessment, in the context of the (recent) history of higher education and research assessment in Italy, starting with a review of the transformation of the relationship between the University and the society. Several social drives are leading the university to a series of transformations, at the national, European and international level. The requirement to use transparency criteria and the associated returns of research spending (in accountability) has become a fundamental issue in informing government, business, citizens and society on the achieved results. The introduction of social impact assessment frameworks is also advancing research agendas towards socially relevant domains, to provide solutions in international competitiveness, social welfare, sustainability and other grand challenges. A terminological and conceptual shift is occurring from a traditional concept of technology transfer and third mission towards a broader meaning of knowledge exchange and co-creation between universities and extra-academic actors and the impact generated. However, this shift towards a transdisciplinary, trans-epistemic and inclusive evaluation framework poses new challenges to capture this complexity, requiring the adoption of new methods and tools presented in this book. The international literature and debate on practices are vital combined with trial-and-error approaches, community involvement, and targeted pilot studies. Beyond controversies, resistances, and easily contrived enthusiasms, this is what this volume tries to investigate.